Rekonstruksi Teknologi Balanced Scorecard dengan Menggunakan Perspektif Khalifatullah Fir Ardh: Suatu Studi Literatur Tentang Bagaimana Visi Organisasi Syariah dapat Menjadi Suatu Aksi - Anwar, Rosyihan; Ghofar, Abdul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
The latest development of syariah business organization issues doesn't take a lead for the improvement of academic researching activity to develop the more accommodative concept of syariah business organization. Research aims at formulating Balanced ScoreCard Syariah (SBSc) through transcendental-structuralism methodology and synthetic process, particularly to reconstruction.Therefore, a humanist, emancipatory, transcendental, and theological design of Balanced Scorecard (BSc) can be ensured.The research uses the perspective of khalifatullah fil ardh to determine the underlying concept or paradigm to match with syariah business organization. This perspective develops from two derivation stages, trusteeship metaphor and zakat metaphor. First strain has been trusteeship metaphor to reconstruct organizational accountability concept, while the second has been zakat metaphor to reconstruct the BSc concept.Three conclusions become evident. First, zakat becomes a main perspective as a foundation as well as an objective for other SBSc perspective.Second, syariah business organization doesn’t merely take responsibility for profit maximizing for shareholders/capital owner, but also distribute the welfare to the nature, human and environment evenly for being accountable to God. Third, Islamic value (tauhid) must be internalized into the vision, objective and every activity of the company such that it may be measured and evaluated within SBSc as main aspect of organization performance.Keywords: Trusteeship Metaphor, Balanced Scorecard, Emancipatory, Humanist, Khalifatullah Fil Ardhperspective, Reconstruction, Balanced Scorecard Syariah, Tauhid, Teleological, Transcendental, Zakat Metaphore